IN SITU X-RAY OBSERVATIONS OF THE DECOMPOSITION OF BRUCITE AND THE GRAPHITE-DIAMOND CONVERSION IN AQUEOUS FLUID AT HIGH PRESSURE AND TEMPERATURE - Okada T.; Utsumi W.; Shimomura O.; Kaneko H.; Yamakata M. (My University, 2002)
An experimental technique to make real-time observations at high pressure and temperature of the diamond-forming process in candidate material of mantle fluids as a catalyst has been established for the first time. In situ X-ray diffraction experiments using synchrotron radiation have been performed upon a mixture of brucite [Mg(OH)2] and graphite as starting material. Brucite decomposes into periclase (MgO) and H2O at 3.6 GPa and 1050 °C while no periclase is formed after the decomposition of brucite at 6.2 GPa and 1150 °C, indicating that the solubility of the MgO component in H2O greatly increases with increasing pressure. The conversion of graphite to diamond in aqueous fluid has been observed at 7.7 GPa and 1835 °C. Time-dependent X-ray diffraction profiles for this transformation have been successfully obtained.